Age-related hearing loss and mild cognitive impairment: a meta-analysis and systematic review of population-based studies. Issue 2 (13th February 2022) - Lau, K; Dimitriadis, P A; Mitchell, C; Martyn-St-James, M; Hind, D; Ray, J
Abstract: Background: The aim of this study was to identify any relationship between hearing loss and mild cognitive impairment. Method: This was a systematic review and meta-analysis of randomised controlled trials conducted using Medline and the Cochrane Library up to 24 June 2020. Prospective, cohort and cross-sectional, and observational studies that reported on the relationship between mild cognitive impairment and hearing loss were included. Results: A total of 34 studies reporting data on 48 017 participants were included. Twenty-three studies observed a significant association between hearing loss and mild cognitive impairment. The pooled risk ratio across all studies of prevalence of mild cognitive impairment in people with hearing loss was 1.44 (random-effects; 95 per cent CI = 1.27–1.64; p < 0.00001; I 2 = 0 per cent). Significantly more people with mild cognitive impairment had peripheral hearing loss compared with those without (risk ratio, 1.40 random-effects; 95 per cent CI = 1.10–1.77; p = 0.005; I 2 = 0 per cent). When the incidence was studied, significantly more people with peripheral hearing loss had mild cognitive impairment compared with those without (risk ratio = 2.06 random-effects; 95 per cent CI = 1.35–3.15; p = 0.0008; I 2 = 97 per cent); however; a high level of statistical heterogeneity was evident. Conclusion: Most of the studies included in this systematic review observed a significant association between hearing loss and mild cognitive impairment.